Metapoetics in Norbert Gstrein's novel The Years to Come (Die kommenden Jahre) - Knežević, Jelena (Primerjalna književnost, 2019)
This article comments on the metapoetic dynamics of the narrative in the novel of the contemporary Austrian writer Norbert Gstrein, The Years to Come (Die kommenden Jahre, 2018) aiming at a more profound understanding of Gstrein's poetics. We first try to define the term metapoetics drawing on the relatively scarce body of scholarship on the topic and relying primarily on Matthias Freise's definition. This is followed by a review of the work of Norbert Gstrein, with a special emphasis on the questions of his poetics raised previously both in his novels and essays. The central part of the paper devoted to the interpretation of the novel analyzes the most prominent instances of metapoetics in the novel: the motto at the beginning, the symbolism of glaciers, the relationship between irony and pathetics suitable to reveal the truth, the central character of the authoress, her literary evening, the insertion of two different versions of chapter 13, as well as other books mentioned in the novel. In conclusion, we summarize the possible answers given by the novel to the questions of poetics the narrative implicitly raises and show how the metapoetic level of the text influences the creation of the meaning of the text.
Keywords: avstrijska književnost; avstrijska proza; Gstrein, Norbert: Die kommenden Jahre; metapoetika; pripovedna struktura; romani